The Effects of Criticism on the Behavioral Improvement Intention of Junior and Senior Secondary School Students: The Role of the Teacher-Student Relationship - Zhang, Feng (Best Evidence in Chinese Education, 2024)
The cultivation of good behavioral habits in students is among the chief goals of school education. The teacher’ praise and criticism play important roles in this process. As opposed to praise, criticism is a negation of student misconduct, which is usually deemed negative feedback by the students criticized, but in the teacher’ eyes, is meant to make them aware of and correct their misbehavior. Currently, there remain divides among researchers on the effects of criticism in the education process. Recruiting 228 8th- and 11th-graders from a middle school and a high school in X City, this study seeks to explore the effects of different types of criticism (outcome, process, and person criticism) on the relationship between the secondary teacher and their students as well as on the latter’s behavioral improvement intention. Also examined is the role of the teacher-student relationship in the relation between the type of criticism and student behavioral improvement intention.